Anesthetic Management for Emergent Repair of Tracheoinnominate Fistula. (26th August 2020) - Nadar, Vinayak; Banik, Ratan K.
Abstract : We present a case of a 30-year-old female, who had tracheostomy revision complicated by false passage into the subcutaneous space and pneumothorax. Six days later, she developed massive bleeding from the mouth, nose, and tracheostomy site. Approximately 2 liters of blood was lost. With high suspicion for tracheo-innominate fistula, she was emergently brought to the operating room for fistula repair. Her anesthetic management was initially focused on maintaining spontaneous ventilation with inhalation agents until surgical exposure was adequate. An endotracheal tube was then placed under guidance of a video-laryngoscope. The tracheostomy tube was then removed over a Cook catheter to maintain secure passage in case of airway collapse. The oral endotracheal tube was then inserted distal to the arterial and tracheal defect. The patient's bleeding was stopped, the fistula was repaired, and she was transferred back to the intensive care unit, but she died several days later due to multi-organ failure.